Using Swarm Intelligence to Solve Bicriteria and Biobjective Machine Scheduling Problems - Faisal, Safanah Y.; Ahmed, Manal G.; Ibrahim, Manal H.; Ali, Faez H. (Iraqi Journal of Science, 2025)
In this paper, solving the Bicriteria Machine Scheduling Problems (BCMSP) and Bi-Objective Machine Scheduling Problems (BOMSP) are proposed using Swarm Intelligence (AI) represented by Particle Swarm Optimization (PSO). The discussed BCMSP is a single machine with maximum early job time and range of late jobs (), and the BOMSP is . Comparison results of a simulation for exact (complete enumeration and Branch and Bound), heuristic method, and simulated annealing with proposed PSO has been made. The results prove the good efficiency of PSO in solving the two problems. All the results obtained by constructing simulation programs using MATLAB language.